E-book technology and its potential applications in distance education - Shiratuddin, Norshuhada; Landoni, Monica; Gibb, Forbes; Hassan, Shahizan (North America, 2006)
The potential for distance learning students to use e-books is explored.E-books are gaining wider interest since the introduction of portable electronic reading devices and software-based readers that provide users with more realistic book reading experiences.The paper discusses where to acquire e-book technology, and how to create e-books.It also reports an evaluation to test the usability of different types of e-book compiler software.By using one of the compilers, the use of e-books to improve the interaction between educators and distance learning students in terms of access to teaching and learning materials and submission of assignments is also demonstrated.